Las consecuencias de Chernobil quince años después - Lutgen, Pierre (Revista Facultad de Ingeniería Universidad de Antioquia, 2001)
An account is done on the many things that have been said about Chemobil nuclear accident. Real consequences are analyzed under the light of similar accidents, observations, studies and reflexions made by the author.